2013
DOI: 10.2106/jbjs.l.00003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infection and Amputation Following Open, Combat-Related Calcaneal Fractures

Abstract: Lower-extremity amputation following open calcaneal fractures is predicted by the injury mechanism, wound location and size, and open fracture type and severity. After short-term follow-up, patients with open calcaneal fractures eventually requiring amputation exhibit improved pain and activity levels compared with patients with continued, ostensibly successful limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…Interestingly, advanced age was not associated with either of these complications. Previous studies with combat-related injuries to the hindfoot and ankle have shown amputation rates as high as 45% [15,16,22]. In contrast to these previous findings, in our study a lower-leg amputation was required in only three patients (2%), reflecting the different nature of this open injury compared to other open injuries of the lower extremity.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Interestingly, advanced age was not associated with either of these complications. Previous studies with combat-related injuries to the hindfoot and ankle have shown amputation rates as high as 45% [15,16,22]. In contrast to these previous findings, in our study a lower-leg amputation was required in only three patients (2%), reflecting the different nature of this open injury compared to other open injuries of the lower extremity.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, younger patients with an open ankle fracture often needed more reconstructive procedures for softtissue coverage and had significantly more complications including chronic pain, probably due to the more severe injury mechanism and initial soft-tissue damage. This finding is in line with previous studies showing that higher Gustilo grade correlates well with the risk of infection and other associated complications of open fractures [4,7,10,16,17].…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, no studies have yet determined the causative pathogens of POWI after operative treatment of calcaneal fractures, although some studies have specified the pathogens for calcaneal osteomyelitis. Overall, these studies reported S. aureus as the main pathogen (19)(20)(21). In a study of infection after all types of orthopedic open fractures, the most frequently identified microorganisms were Enterobacter species and Pseudomonas (31%), followed by Enterococcus species in 27% of cases (22).…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue and osseous infections accounted for over 25% and 35% of all complications in the pre-amputation and postamputation time periods, respectively. The high rate of infection is comparable to similar studies evaluating similar patient cohorts and may give pause to surgeons and limb salvage patients who desire an amputation as a means to eradicate infection [7,18,21,[27][28][29][30]. In fact, Melcer et al showed that late amputees actually had higher rates of infectious complications and nonhealing wounds compared to limb salvage patients and acute amputees [18].…”
Section: Discussionmentioning
confidence: 61%